TERRITORIAL SETTLEMENT AND CLAN DIVISIONS OF THE LULIS IN THE SURKHAN OASIS - Mashxura Ruziyeva (Western European Studies, 2025)
In the Surkhandarya Oasis, the lifestyle and occupations of the Lulis have undergone significant changes over the centuries under the influence of the ethno-cultural environment of surrounding peoples. In the studied region, shifts in the Lulis’ way of life and daily activities have played an important role in improving their economic conditions. As they acquired labor skills and adapted to new types of economic activities, the number of impoverished and destitute Lulis began to decrease significantly. This article analyzes the changes in the material and spiritual culture of the Lulis in the Surkhan Oasis.
Keywords: Lulis; Surkhan-Sherobod; Denov